Photocell contact mat: A new instrument to measure contact and flight times in running - Viitasalo, J. T.; Luhtanen, P.; Mononen, H. V.; Norvapalo, K.; Paavolainen, L.; Salonen, M. (Journal of Applied Biomechanics, 1997)
A new instrument, the photocell contact mat (PCM), was developed to measure ground contact time and flight time as well as step and stride frequency as a function of running time or running distance. The purpose of this study was to evaluate the validity and accuracy of PCM measurements against simultaneous force platform measurements. Effects of striking pattern (sprinter or long-distance), running velocity, and height of the PCM from ground level on the contact parameters were analyzed. One male sprint runner and one male distance (marathon) runner volunteered as subjects. The time difference between the PCM and force platform determinations linearly increased as a function of the PCM height and decreased as a function of running velocity (except for the lowest 10 mm PCM height). The low coefficients of variation found between corrected PCM contact times and force platform contact times suggested that the PCM is an accurate instrument to measure ground contact times.